2015
DOI: 10.1515/msac-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Evaluation of Surface Cleaning Preparation Using Different Test Methods / Virsmu tīrīšanas līdzekļa toksiskuma novērtēšana, izmantojot dažādas testa metodes

Abstract: -Surface cleaning preparations pose a serious threat to the environment. Toxicity of a pre-manufactured preparation SCP-1 was tested on bacteria, algae and higher plants and was expressed as a minimal inhibitory concentration (MIC). Obtained results showed that among unicellular and more complex testorganisms MIC values differed 10-100 fold suggesting that an application of complex test-organism battery is necessary to evaluate the toxicity of SCP-1 thoroughly. MIC values were different from the critical micel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The WF used in this study, belongs to the market group of surface care products and possesses a strong antibacterial effect, most probably due to the presence of different QACs. Our previous studies showed its inhibition effect for a battery of test-organisms, ranging the MIC values in the following order: Thamnocephalus platyurus (0.001%)>Selenastrum capricornutum (0.01%)>P.fluorescens (0.05%)>Lepidium sativum (0.6%) [24].…”
Section: Discussionmentioning
confidence: 95%
“…The WF used in this study, belongs to the market group of surface care products and possesses a strong antibacterial effect, most probably due to the presence of different QACs. Our previous studies showed its inhibition effect for a battery of test-organisms, ranging the MIC values in the following order: Thamnocephalus platyurus (0.001%)>Selenastrum capricornutum (0.01%)>P.fluorescens (0.05%)>Lepidium sativum (0.6%) [24].…”
Section: Discussionmentioning
confidence: 95%